TRAIL-conjugated silver nanoparticles sensitize glioblastoma cells to TRAIL by regulating CHK1 in the DNA repair pathway. (1st December 2020) - Sur-Erdem, Ilknur; Muslu, Kerem; Pınarbası, Nareg; Altunbek, Mine; Seker-Polat, Fidan; Cingöz, Ahmet; Aydın, Serdar Onur; Kahraman, Mehmet; Culha, Mustafa; Solaroglu, Ihsan; Bagcı-Önder, Tugba
ABSTRACT: Objectives: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) selectively triggers apoptosis in cancer cells, but not in normal cells. Resistance of glioblastoma cells to TRAIL is a major obstacle for successful clinical treatment of TRAIL. Thus, there is an essential requirement for novel approaches to sensitize TRAIL resistance. Silver nanoparticles (AgNPs) are one of the most promising nanomaterials that show immense antitumor potential via targeting various cellular and molecular processes; however, the effects of AgNPs on TRAIL sensitivity in cancer cells remain unclear. Therefore, we hypothesized that TRAIL-conjugated AgNPs (TRAIL-AgNPs) can overcome TRAIL resistance through inducing death receptor activation in glioblastoma cells, but not normal cells. Methods: In this study, the therapeutic effect of TRAIL-AgNPs is investigated by analyzing the cell viability, caspase activity, and CHK1 gene expression in T98 G TRAIL-Sensitive (TS) and T98 G TRAIL-Resistant (TR) glioblastoma cells. Results: It is found that TRAIL-AgNPs are more toxic compared to TRAIL and AgNPs treatments alone on TR cells. While TRAIL and AgNPs alone do not enhance the caspase activity, conjugation of TRAIL to AgNPs increases the caspase activity in TR cells. Moreover, the TRAIL-AgNPs–treated TR cells show less CHK1 expression compared to the TRAIL treatment. Conclusion: These results suggest that TRAIL sensitivity of TR cells can be enhanced by conjugation of TRAIL with AgNPs, which would be a novel therapeutic approach to sensitize TRAIL resistance.